2018
DOI: 10.1002/jmri.26575
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of proton density fat fraction measurement across field strengths and scan intervals: A phantom and human study

Abstract: Background Complex‐based chemical shift imaging‐based magnetic resonance imaging (CSE‐MRI) is emerging as a preferred method for noninvasively quantifying proton density fat fraction (PDFF), a promising quantitative imaging biomarker (QIB) for longitudinal hepatic steatosis measurement. Purpose To determine linearity, bias, repeatability, and reproducibility of the PDFF measurement using CSE‐MRI (CSE‐PDFF) across scan intervals, MR field strengths, and readers in phantom and nonalcoholic fatty liver disease (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…Concordant with our findings, a recent phantom study showed high precision of PDFF measurements (mean bias of 0.22 PDFF%) obtained with imagers from multiple different vendors and at both 1.5T and 3.0T across multiple sites. 25 In patients, previous studies on steatosis quantification have shown high linear correlation and small mean bias in MRIdetermined PDFF ranging from 0.9-3.7% across two 26,27 and three 28 different MRI platforms. In our study, the reproducibility of MRI-determined PDFF in lumbar bone marrow was comparable to or even better than that reported for liver fat quantification, possibly owing to the inherent heterogeneity of steatosis across the liver (ie, because of different ROI locations).…”
Section: Discussionmentioning
confidence: 94%
“…Concordant with our findings, a recent phantom study showed high precision of PDFF measurements (mean bias of 0.22 PDFF%) obtained with imagers from multiple different vendors and at both 1.5T and 3.0T across multiple sites. 25 In patients, previous studies on steatosis quantification have shown high linear correlation and small mean bias in MRIdetermined PDFF ranging from 0.9-3.7% across two 26,27 and three 28 different MRI platforms. In our study, the reproducibility of MRI-determined PDFF in lumbar bone marrow was comparable to or even better than that reported for liver fat quantification, possibly owing to the inherent heterogeneity of steatosis across the liver (ie, because of different ROI locations).…”
Section: Discussionmentioning
confidence: 94%
“…Nasr et al[ 6 ] found that 1 H-MRS had a specificity of 100% and sensitivity of 79% with a PDFF cut-off value of 3%, a specificity of 94% and sensitivity of 87% with a PDFF cut-off value of 2%. Although recognized as the most accurate noninvasive tool to assess PDFF quantitatively, MRS is limited to its device- and operator-dependency, complexity, and potentially errors[ 71 ]. Complex-based chemical shift imaging-based MRI (CSE‐MRI) is regarded as a promising method to quantify PDFF, which could quantitatively assess liver fat content with a refined pulse sequence[ 72 - 74 ].…”
Section: Diagnosis Of Nafldmentioning
confidence: 99%
“…Complex-based chemical shift imaging-based MRI (CSE‐MRI) is regarded as a promising method to quantify PDFF, which could quantitatively assess liver fat content with a refined pulse sequence[ 72 - 74 ]. It exhibits a high correction with MRS‐PDFF ( r 2 = 0.985 for 1.5 T MR systems, r 2 = 0.991 for 3.0 T MR systems)[ 71 ]. MR diffusion weighted imaging (DWI) measures motion of water protons diffusing and tissue perfusing[ 75 , 76 ] and is regarded another promising tool for assessing liver fat content[ 77 ], while it exerts poor performance for detecting steatosis in comparison with MRS and dual echo in phase and out of phase imaging[ 78 ].…”
Section: Diagnosis Of Nafldmentioning
confidence: 99%
“…PDFF measurements have been previously compared between 1.5T and 3T, using different manufacturers [16][17][18][19][20]. The largest comparison cohort across manufacturers was in n = 24 obese individuals which made a comparison of 1.5T Ingenia Philips, 3T Ingenia Philips and 3T 750 W GE.…”
Section: Introductionmentioning
confidence: 99%
“…The mean bias associated with field strength for this meta-analysis was -1.2%. Other smaller cohorts have compared normal individuals against phantoms, diabetics against non-diabetics and children, with biases varying between -0.4 to +1.2% [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%